High serum uric acid levels are associated with increased prevalence of gallstones in adult women: a cross-sectional study based on NHANES - Lv, Guozheng; Wang, Decai; Huang, Yu; Shi, Ruizi; Qin, Chuan; Chen, Xi; Zeng, Xintao; Luo, Hua; Yang, Pei; Chen, Sirui; Wang, Jianjun (Frontiers in Medicine, 2025)
ObjectiveWe investigated the association between serum uric acid (SUA) levels and gallstone (GS) prevalence in adult women.MethodsParticipants' information were taken from the United States National Health and Nutrition Examination Survey (2017–2020). Logistic regression analysis and dose-response curve were used to assess the association between SUA levels and the prevalence of GS in adult women. Subgroup analyses were performed to investigate associations between SUA levels and age, ethnicity, body mass index, hypertension, and diabetes.ResultsA total of 600 participants self-reported a history of GS. After adjusting for confounding, the prevalence of GS in adult women increased by 14% for every 1 mg/dL increase in SUA (odds ratio [OR]: 1.14, 95% confidence interval [CI]: 1.06, 1.22). Testing SUA as a categorical variable for sensitivity analyses indicated a 1.6-fold increase in the prevalence of GS in tertile 3 (OR=1.60, 95% CI: 1.25, 2.04) compared to tertile 1. Dose-response curves showed a nonlinear correlation between SUA levels and the prevalence of GS. Subgroup analyses indicated that SUA level was associated with an increased prevalence of GS in most subgroups, although subtle differences existed.ConclusionSUA was positively and non-linearly associated with the prevalence of GS in adult females. Despite the inability to clarify the causal relationship between them, our results remain interesting.